Contradictions and Inconsistencies in Human Nature: Evidence from Yorùbá Proverbs - Timothy Adeyemi Akanbi (Journal of Language and Literature, 2020)
Yorùbá proverbs, and by extension, proverbs in every culture and clime, show the beliefs, philosophy, traditions, and norms of every society.  There is no community or society where proverbs are not in use.  Proverb is a phenomenon that aligns with the wisdom of people livingwithin a community.  The Yorùbá race holds proverbs in high esteem.  They see it as a culture that cuts across all the strata of the society.  For every deed, action or interaction, there is always a make-ready proverb that matches it.  This paper examines Yorùbá proverbs but in a different perspective.  It looks at the seeming contradictions observed in Yorùbá proverbs and brings to the fore the implications of such contradictions.  The paper also examines the paradox of these contradictions and affirms that the nature of man calls for the different proverbs that match the behaviors of people.  The paper also asserts that this phenomenon is to exemplify the dynamics, functions and usages of language in general and of the Yorùbá language in particular.  The paper concludes that the seeming contradictions observed in Yorùbá proverbs portray the nature of inconsistencies and contradictions in man.  The paper, therefore, opines that it is not that proverbs are contradictory on their own, but that the proverbs portray unpredictable behaviors that are found in human nature.